Genome-wide alterations in CpG island methylation induced by arsenite - Christensen, Brock C.; Marsit, Carmen J.; Welsh, Marleen M.; Nelson, Heather H.; Kelsey, Karl T. (European Journal of Oncology and Environmental Health, 2017)
Aberrant methylation of tumour suppressor CpG islands, resulting in epigenetic gene silencing, is common in human cancer. However, the mechanism responsible for inducing gene silencing remains unclear. Epidemiologic data have confirmed that the human carcinogen arsenic is associated with epigenetic silencing in several tumour-types. In this study, we set out to investigate the role exposure to arsenic plays in inducing CpG island methylation. To test the effects of the USA Environmental Protection Agency’s drinking water arsenic limits (10 ppb), two clonal populations of immortalized human keratinocytes were treated with this level of arsenic, and methylation at CpG islands was compared to pooled, untreated keratinocytes using a 12K genome-wide CpG microarray. Islands with at least a 1.5-fold increase or decrease in methylation were examined. Comparing arrays from duplicate treated, clonal populations, a global decrease in methylation was seen, that involved more than 3000 CpG island loci, with a concomitant increase in methylation at over 500 CpG loci. Between arrays, the specific loci that exceeded the methylation change cutoff had > 99% concordance, demonstrating both reproducibility and specificity. Consistent with alterations from human tumours, this pattern of globally decreased CpG island methylation and local CpG island hypermethylation suggests that arsenic contributes to epigenetic alterations in human cancer.